In situ microanalysis of organic colorants by inkjet colloid deposition surface‐enhanced Raman scattering. (20th December 2013) - Benedetti, Dario P.; Zhang, Jie; Tague, Thomas J.; Lombardi, John R.; Leona, Marco
<x xml:space="preserve">Abstract</x> We present a new method for the minimally invasive in situ identification of inks and colorants on documents and other objects on the basis of the deposition of silver colloid nanodroplets on a region of interest in the objects to be tested using inkjet technology. By adapting commercially available thermal and piezoelectric inkjet heads, volumes of silver colloid in the 60–220 picoliters range (corresponding to impact diameters in the range of 50–150 µm) can be delivered onto substrates with great accuracy and precision. We demonstrate that the instantaneous superheating of the colloid in the thermal print head does not adversely affect the surface‐enhanced Raman spectroscopy efficiency of the Ag nanoparticles. Furthermore, by mounting a compact piezoelectric inkjet head within a large‐stage Raman microscope, we developed an instrument where all phases of surface‐enhanced Raman spectroscopy microanalysis are integrated, with great advantages in sample handling, spatial accuracy, and colloid delivery reproducibility. The approach can be considered functionally nondestructive as the amount of silver delivered, and the area affected are too small to be detected by visual observation, and in most conditions, even by optical microscopy. The method was successfully applied to the analysis of textile fibers, gel pen ink writing on paper, and a Japanese woodblock print dating to the end of the 19th century. Copyright © 2013 John Wiley & Sons, Ltd.